Detecting World War II bombing relics in markedly transformed landscapes (city of Most, Czechia) - Dolejš, Martin; Samek, Vojtěch; Veselý, Martin; Elznicová, Jitka (Applied geography (Sevenoaks), 2020)
Landscapes carrying remnants of military activity gain greater attention in many fields of research due to intrinsic cultural and natural values as well as hazard of unexploded ordnance (UXO). Identification of military remnants is currently facilitated by the use of high precision LiDAR-derived digital terrain models. Contribution of these models to identification of military remnants is unfortunately of limited use in heavily transformed environment such as post-mining landscapes. Therefore, other approach and sources needs to be employed. We present the results of the extensive study of archival sources, plans and maps, which led to determination of geographical dimension of devastation of the prominent target of allied attacks in Czechia during the World War II - Sudetenländische Treibstoffwerke (STW). Besides the framing of allied bombing in the historical context, we found out and delimited possible remnants of the landscape alternation by bombing in the industrial landscape nowadays markedly transformed. Unreferenced archival aerial imagery, dated shortly after the War ended and yet unpublished and unprocessed, and bombing plans (archival field mapping) were photogrammetrically processed and analysed in GIS in order to localize particular craters. The database of impacts was consecutively confronted on unaltered minor part of our study area with present-day high-precision digital terrain model (DTM) based on LiDAR scanning that revealed the extant craters. We have identified more than 15 thousand craters, the spatial distribution of which indicates relative inaccuracy of bombing. Despite the heavy transformation of the terrain, the mixed method approach also revealed the localities with preserved craters that are susceptible to UXO excavation risk. Overall, the study provided an empirical survey that explored and tested the use and accuracy of archival sources for bombing craters detection, being often the only available source in heavily transformed terrains. •Mixed-methodology for assessment of spatial extent of bombing distribution is presented.•Crater identification could be distorted by specific mining landforms.•LiDAR visualization reveal the bombing remnants outside heavily transformed landscape.•The precision of the bombing was not accurate, but not worse than cases from similar time.